Research and Analysis of Library Access Control Authentication Scheme Based on IPv6 and Location Technology. Issue 4 (May 2019) - Li, Panfeng; Wei, Jiangshu; Zhang, Di; Hu, Lin; Hu, Qiyao
Abstract: With the maturity of IPv6 technology, smart campus has become a trend, and the management of libraries will inevitably become intelligent. Nowadays, libraries in many colleges and universities use the method of swiping for identity authentication, which has great drawbacks. In order to solve the defects of traditional access control technology, this paper proposes a library access control authentication scheme based on IPv6 and location technology: this scheme realizes identity authentication through IPv6 wireless local area network and WIFI positioning technology, effectively avoiding a series of authentication problems.